Evolution of The Omnichannel Concept in DIY Retail Chains - Mariusz WOŹNIAKOWSKI; Marcin KŁAK (Communications of International Proceedings, 2022)
The dynamics of technology development influence the changing needs and purchasing behavior of customers. This is one of the reasons why retail chains invest in researching and implementing new tools to support and stimulate the purchasing process. Digital solutions, combined with the development of e-commerce, dominate. However, the impact of digital solutions on traditional distribution channels is also visible. These types of changes fit into the omnichannel concept, which is characterized by combining channels of online and offline sales, giving the customer a consistent and shared experience with the seller’s brand. This article tries to identify multi-channel sales among retail chains in the renovation and construction industry (DIY, Do It Yourself) operating in Poland. In the beginning, reference was made to the essence of the omnichannel concept based on the literature. The market analysis results in terms of the use of tools that fit into the omnichannel concept among DIY networks are presented below. The analysis was conducted twice in three years. The first was carried out in December 2019 (time before the pandemic), and the second was in March 2022 (after the pandemic). The conducted analysis showed to what extent the commercial networks in the renovation and construction industry present in Poland use selected solutions that fit into the omnichannel concept and attempts to indicate the direction of further changes.
Keywords: Omnichannel; DIY; Do It Yourself Networks; Retail Chain